1) 25 - b^2 - 2b^2 + 6b = - 3b^2 + 6b + 25
2) - 5y^2 - 15 + y^2 - 8y + 16 = - 4y^2 - 8y + 1
3) 3( x^2 - 4x + 4) - 3x^2 = 3x^2 - 12x + 12 - 3x^2 = - 12x + 12
1) ( 3x - x^3)(3x + x^3)
2) ( x^2 - 3)^2
8y^3 - 1^3 - y( y^2 - 1) = 8y^3 - 1 - y^3 + y = 7y^3 + y - 1
При y = 1,5:
7y^3 + y - 1 = 7*3,375 + 1,5 - 1 = 23,625 + 1,5 - 1 =24,125
4. 1) ( x - 8 - 5y^2)(x - 8 + 5y^2)
2) ( a - b)(a + b) - ( a - b) = ( a - b)(a + b - 1)
3) ( x^2 - 2)(x^4 + 2x^2 + 4)
5) a^2 + 2ab + b^2 + a^2 - 2ab + b^2 = 2a^2 + 2b^2
2a^2 + 2b^2 = 2a^2 + 2b^2 - верно,тождество доказано.